Knowledge Management as an Alternative for Developing Arabic Teaching Based on Religious Moderation: Implications for Islamic Boarding Schools in Madura - Jailani, Mohammad (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2023)
This was motivated by the launch of the religious moderation policy by the Minister of Religion Gus Yaqut Cholil Qoumas, as well as the implementation of the independent curriculum policy, the Merdeka campus, and the driving school by Nadiem Makarim (Minister of Education and Culture). Indonesia is experiencing significant development and dynamics of change. According to online news, and reference research from Google Scholar, and Scientific Direct, data on Islamic boarding school learning and education is very high. However, on the other hand, 80% of the education in Islamic boarding schools or non-formal institutions has decreased. This study aims to increase religious moderation in Madura Islamic boarding schools, in learning Arabic, the yellow book, and ta'limu' mutaallim culture with a knowledge management approach. Naturalization in this research is based on a qualitative descriptive case study in a Madura Islamic boarding school. This means that researchers are dealing directly (directly) with the research location, with the methods of interview, observation, and documentation. The subjects of this study consisted of clerics, ustadz, policymakers (community leaders), and students. For this reason, that research is more objective, credible, and reliable. The data analysis technique used is based on Miles and Huberman's research theory. Namely data display, data reduction, data presentation, and data verification. The analytical knife is strengthened by triangulation techniques, namely researchers in processing and analyzing data until they are saturated (perfect). The results of this study describe the concept of religious moderation that needs to be introduced and conveyed to the Madurese community, especially the santri. With a knowledge management approach (knowledge management), namely implementing mufradat and fasohah literature related to religious moderation. Among them, students are given insight, counseling guidance, and spiritual moderation (wasatiyah). The Ustadz are at the facility by participating in comparative studies, workshops, strengthening education quality management, and training in Arabic learning. on the one hand, so that students can accept religious tolerance and moderation. Because basically in Madura it is very close and closely related to problems of understanding, for example between NU and Muhammadiyah, therefore one alternative is language Arabic learning based on religious moderation which is strengthened by knowledge management in the world of Islamic boarding schools.